2020
DOI: 10.1029/2020jb019677
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of the Aleutian‐Alaska Subduction Zone Revealed by Full‐Wave Ambient Noise Tomography: Implications for the Along‐Strike Variation of Volcanism

Abstract: The along-strike variations of the velocity, thickness, and dip of subducting slabs and the volcano distribution have been observed globally. It is, however, unclear what controls the distribution of volcanoes and the associated magma generation. With the presence of nonuniform volcanism, the Aleutian-Alaska subduction zone (AASZ) is an ideal place to investigate subduction segmentation and its relationship with volcanism. Using full-wave ambient noise tomography, we present a high-resolution 3-D shear wave ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
75
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(87 citation statements)
references
References 107 publications
(202 reference statements)
8
75
3
1
Order By: Relevance
“…Serpentinization of the Aleutian forearc has been reported by several existing seismic tomography studies (e.g., Martin‐Short et al., 2018; Yang & Gao, 2020). The vertical cross‐section B‐B' (Figure 8b) indicates reduction in shear wave velocity at the forearc near the Kodiak island and the 15 km Vs slice shows the region has the most significant Vs reduction than elsewhere, probably infers more fluid‐saturated material.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Serpentinization of the Aleutian forearc has been reported by several existing seismic tomography studies (e.g., Martin‐Short et al., 2018; Yang & Gao, 2020). The vertical cross‐section B‐B' (Figure 8b) indicates reduction in shear wave velocity at the forearc near the Kodiak island and the 15 km Vs slice shows the region has the most significant Vs reduction than elsewhere, probably infers more fluid‐saturated material.…”
Section: Discussionmentioning
confidence: 68%
“…Indeed, thermal modeling studies (e.g., Abers et al., 2017) have suggested low temperature in the Aleutian mantle forearc, providing the environment for the serpentinization process. Previous tomographic studies also suggested that the Aleutian forearc is low in seismic velocities (e.g., Eberhart‐Philllips et al., 2006; Martin‐Short et al., 2018; Yang & Gao, 2020), which further increase the possibility of serpentinization of the Aleutian forearc. The imaged serpentinized region could be physically related to the seismicity gap (Figure 8b), as serpentine generally exhibits stable‐sliding aseismic behavior in the laboratory (e.g., Peacock & Hyndman, 1999).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our model reveals strong structural variations within eastern North America. It has been demonstrated that more data and/or a more accurate methodology result in stronger velocity contrasts (e.g., Hung et al., 2004; Becker, 2012; Gao & Shen, 2014; Gao, 2018; Gao et al., 2020; Savage et al., 2017; Yang & Gao, 2020). Furthermore, we ignore seismic anisotropy and attenuation in wave simulation and inversion.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporation of P ‐wave velocities in kernel calculation and inversion provides additional constraints for the shallow crust, which significantly reduces the influence of P ‐wave velocity uncertainties on deeper structures. We invert for the shear velocity perturbations based on a damped least squares scheme (Montelli et al., 2004; Gao & Shen, 2014; Yang & Gao, 2020), with the damping and smoothing parameters selected in terms of the tradeoff between model norm and variance reduction (Figure ). The velocity model was progressively and iteratively updated for a total of six iterations (Figures and ).…”
Section: Methodsmentioning
confidence: 99%